Blessed be intelligent assistance systems at high task rotation?: The effect on motivational work design in assembly - Walczok, Marvin; Bipp, Tanja (Human factors and ergonomics in manufacturing & service industries, 2024)
We aimed to provide causal evidence on the contradictory effects of projection-based intelligent assistance systems (IASs) for nine motivational work characteristics (MWCs). IASs are increasingly implemented in assembly to counteract rising cognitive workload due to individualized manufacturing processes. However, how IASs enhance or restrict MWCs is largely unknown. We conducted two studies with experimental vignette methodology. In Study 1 (N1 = 169 German employees), we manipulated an assembly workplace (with IAS vs. without IAS) and tested whether findings indicating only positive effects of IASs in the support of a simple assembly process can be transferred to more complex assembly processes. In Study 2 (N2 = 176 German employees), we manipulated again the assembly workplace (with IAS vs. without IAS) and in addition the dynamic of product changes (task rotation after 1 h vs. no task rotation). Analyzing the data with SPSS 27, we found increased feedback from job and information processing and decreased work scheduling, decision-making, and work methods autonomy when working with IAS. In Study 2, we did not find the main or interaction effects of task rotation on MWCs. Our experimental evidence suggests that working with IASs represents a double-edged sword regarding MWCs and that the effect of task rotation is limited. Hence, our results provide vital theoretical implications for a much-needed work design theory that delineates how new technologies shape work design and practical implications for modern assembly.
Gesehen am 26.02.2024